The Effect of Multidisciplinary Approach on the Birth Rate of Fetuses with Prenatally Diagnosed Congenital Heart Disease - Kim, Susan Taejung (J Korean Med Sci, 2019)
BACKGROUND: This study aimed to determine the effect of a multidisciplinary approach on the birth rate of fetuses with prenatally diagnosed congenital heart diseases (CHDs). METHODS: Among the fetuses of 724 gravidas who underwent fetal echocardiography in Samsung Medical Center from January 2013 to June 2017, 463 fetuses with normal cardiac structure, arrhythmia or simple left-to-right shunt were excluded, and the remaining 261 were included in the study. The subjects were subdivided into groups based on whether they were consulted multidisciplinarily, that is, consulted simultaneously by pediatric cardiologists, obstetricians and pediatric cardiac surgeons or not. They were also categorized based on the initial fetal echocardiogram results. RESULTS: Among the fetuses in the multidisciplinary group, 64.5% of the fetuses were given birth to, and the proportion was not different from that in the non-multidisciplinary group (68.6%, P = 0.48). The delivery rate in the multidisciplinary consultation group were 69.2% in the transposition of the great arteries group, 63.6% in the tetralogy of Fallot group, 68.8% in the pulmonary atresia or interrupted aortic arch group, 62.5% in the coarctation of aorta group, 60.0% in the atrioventricular septal defect group, 70.0% in the functional single ventricle group, and 55.6% in the hypoplastic left heart syndrome group; there were no significant differences between the 10 echocardiogram groups. However, when the subjects were categorized into Fontan repair group and biventricular repair group, the Fontan repair group showed a significant increase in the likelihood of delivery when a multidisciplinary approach was taken (P = 0.035). CONCLUSION: When a fetus was diagnosed with a CHD where Fontan repair should be considered, a multidisciplinary approach resulted in increased possibility of delivery.